Model pseudopotential of the electron – negative ion interaction - Rudavskii, Yu.; Ponedilok, G.; Klapchuk, M. (Condensed Matter Physics, 2003)
Generalization of the Anderson model to describe the states of electronegative
impurities in liquid-metal alloys is the main aim of the present paper.
The effects of the random inner field on the charge impurity states
is accounted for selfconsistently. Qualitative and quantitative estimation of
hamiltonian parameters has been carried out. The limits of the proposed
model applicability to a description of real systems are considered. Especially,
the case of the oxygen impurity in liquid sodium is studied. The modelling
of the proper electron-ionic interaction potential is the main goal of
the paper. The parameters of the proposed pseudopotential are analyzed
in detail. The comparison with other model potentials have been carried
out. Resistivity of liquid sodium containing the oxygen impurities is calculated
with utilizing the form-factor of the proposed model potential. Dependence
of the resistivity on impurity concentration and on the charge states
is received. Узагальнюється мікроскопічна модель Андерсона з метою опису
станів електронегативних домішок у розплавах рідких металів. Самоузгоджено враховується вплив випадкового внутрішнього поля
на зарядові стани домішки. Проведена якісна і кількісна оцінка параметрів гамільтоніана, досліджуються межі застосовності мікроско-
пічної моделі до опису конкретних систем. Розглянуто конкретний
випадок домішки кисню в рідкому натрії. У такій системі важливим є
вибір потенціала взаємодії електронів з домішками. Детально проаналізовано параметри запропонованого псевдопотенціала, проведено порівняння з іншими модельними псевдопотенціалами. Використавши форм-фактор запропонованого потенціала, пораховано
питомий опір рідкого натрію з домішками кисню. Отримано залежність домішкового питомого опору від зарядового стану домішок та
їх концентрації.